Apakah Media Pembelajaran Berbasis Android Efektif Untuk Mengeksplor Kemampuan Spasial Siswa? - Evi Latifatus Sirri; Nani Ratnaningsih; Puji Lestari (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
The aims of this study is to produce android-based learning media on building materials to explore spatial abilities and to determine the quality of the effectiveness of students' spatial abilities after using these learning media. The research subjects were material experts, media experts, mathematics teachers and 25 students of MTs Al-Ishlah Cihaurbeuti class VIII. The research method used is R&D with Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. Data collection techniques used in this study were observation, unstructured interviews, tests and questionnaires. Meanwhile, the instruments used are spatial ability test questions, material expert validation sheets and media experts, student and teacher response questionnaires. This study resulted in an android-based learning media that was packaged in the form of an application (.apk) on solid figure material to explore spatial abilities and was in the valid category very suitable for use for junior high school students. The resulting product is effective for exploring spatial abilities as seen from the calculation of Effect Size with a value of 1.32 in the "strong effect" category. This means that the learning media can be used as a learning resource to support mathematics learning in solid figure materials.